Experiment and Numerical Simulation of Strength and Stress Distribution Behaviors of Anchored Rock Mass in a Roadway. (12th April 2023) - Zhao, Honghui; Su, Haijian; Qin, Xiaofeng; Zhang, Kai; Jiang, Yu; Wang, Wenbo
Abstract : Due to the influence of the ground stress, mining disturbance, and other factors, the roadway surrounding rock in deep underground engineering such as mines, tunnels, and underground caverns is prone to looseness and deformation with the excavation of roadways. In such engineering, the bolt support is frequently employed to stabilize the surrounding rock. In this work, a part of the anchor and the surrounding rock were taken as a simplified model of the anchorage rock mass, and the laboratory compression test was performed on the similitude model. Then, the FLAC3D software was used to simulate varying numbers of bolts and different lateral pressure conditions, and the peak stress, the maximum principal stress field, and the anchor stress field distribution of the anchorage rock mass were obtained. The influence of bolt pretightening force and row spacing on the stability of surrounding rock was discussed using the combined arch theory. The results show that increasing the number of bolts and lateral pressure in the anchorage rock mass can significantly improve the stress value and distribution range of the maximum principal stress field and the anchorage stress field. The fluctuation of the anchorage stress field at different anchorage distances can be lessened by increasing the number of bolts (bolt density). When the lateral pressure exceeds 3 MPa, the anchorage mechanical characteristics of the anchorage rock mass tend to remain stable. The coverage of the effective anchorage stress field and the thickness of the surrounding rock anchorage composite arch can be increased by increasing the bolt pretightening force and decreasing row spacing, consequently improving the anchorage mechanical characteristics of the anchorage rock mass. The research results can be used as a theoretical reference for choosing appropriate bolt support parameters for the roadway surrounding rock.